Sudden cardiac death risk stratification - Deyell, Marc W; Krahn, Andrew D; Goldberger, Jeffrey J (Circulation research, 2015)
Arrhythmic sudden cardiac death (SCD) may be caused by ventricular tachycardia/fibrillation or pulseless electric activity/asystole. Effective risk stratification to identify patients at risk of arrhythmic SCD is essential for targeting our healthcare and research resources to tackle this important public health issue. Although our understanding of SCD because of pulseless electric activity/asystole is growing, the overwhelming majority of research in risk stratification has focused on SCD-ventricular tachycardia/ventricular fibrillation. This review focuses on existing and novel risk stratification tools for SCD-ventricular tachycardia/ventricular fibrillation. For patients with left ventricular dysfunction or myocardial infarction, advances in imaging, measures of cardiac autonomic function, and measures of repolarization have shown considerable promise in refining risk. Yet the majority of SCD-ventricular tachycardia/ventricular fibrillation occurs in patients without known cardiac disease. Biomarkers and novel imaging techniques may provide further risk stratification in the general population beyond traditional risk stratification for coronary artery disease alone. Despite these advances, significant challenges in risk stratification remain that must be overcome before a meaningful impact on SCD can be realized.